Visi Kosmopolitanisme Islam di Lingkungan Jaringan Intelektual Muda Muhammadiyah - Bachtiar, Hasnan; Fadly, Haeri; Nurhakim, Moh. (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
This paper tries to diagnose the vision of Islamic Cosmopolitanism toward the circle of Young Intellectual Muhammadiyah Network (JIMM). Through the perspective of social diagnose of the tradition of Mannhemian sociology of knowledge, it finds that JIMM has their own intellectual stand amongst some humanity discourses and ideas such pluralism, multiculturalism, bhinneka nationalism and cosmopolitanism. Elaborations among these discourses and ideas are played in order to serve the sense of social justice and humanity, as well as human dignity in the world. These elaborations are dakwah efforts that want to be a winner in the midst of global civilization constellation. However, in these attitudes, JIMM has foundation of thought which is interpreted into three ways, are: progressive Islam, social liberation, and historical activism. In dealing with very different context of Muslim societies in the contemporary time, Islamic Cosmopolitanism of JIMM attempts to fulfill their mission through the agenda of internationalization Islam berkemajuan and Indonesian Islam.